The Impact of the Term Auction Facility on the Liquidity Risk Premium and Unsecured Interbank Spreads - Olav Syrstad (Norges Bank, 2014)
This paper investigates the effectiveness of the Federal Reserve's Term Auction Facility (TAF) in alleviating the liquidity shortage in USD and reducing the spread between the 3-month Libor rate and the expected policy rate. I construct a proxy for the 3-month liquidity risk premium based on data from the FX forward market which enables me to (i) decompose the Libor spread into a liquidity premium and a credit premium, and (ii) test the effectiveness of the TAF in reducing the liquidity premium in money market spreads. I find that long-term (84-day) TAF auctions were effective in reducing the 3-month liquidity premium. Furthermore, a reduction in the liquidity premium led to a fall in the 3-month Libor spread in USD. Credit risk, however, seems to have been a rather modest factor in explaining the increase in the Libor spread during the financial crisis.
hdl:11250/2495978
Keywords: E41; E43; E51; 330; LIBOR-OIS spread; term auction facility; liquidity premium; credit premium